Light-Time Effect and Mass Transfer in the Triple Star SW Lyncis - Chun-Hwey Kim (Journal of Astronomy and Space Sciences, 1999)
In this paper all the photoelectric times of minimum for the triple star SW Lyn have been analyzed in terms of light-time e ect due to the third-body and secular period decreases induced by mass transfer process. The light-time orbit determined recently by Ogloza et al.(1998) were modi ed and improved. And it is found that the orbital period of SW Lyn have been decreasing secularly. The third-body revolves around the mass center of triple stars every 5y.77 in a highly eccentric elliptical orbit(e=0.61). The third-body with a minimum mass of 1.13M may be a binary or a white dwarf. The rate of secular period-decrease were obtained as ¡âP/P = -12.45 x 10^-11, implying the mass-transfer from the massive primary star to the secondary. The mass losing rate from the primary were calculated as about 1.24 x 10^-8M /y. It is noticed that the mass-transfer in SW Lyn system is opposite in direction to that deduced from it's Roche geometry by previous investigators.